2012
DOI: 10.2147/ijn.s31723
|View full text |Cite
|
Sign up to set email alerts
|

Cell-penetrating superoxide dismutase attenuates oxidative stress-induced senescence by regulating the p53-p21Cip1 pathway and restores osteoblastic differentiation in human dental pulp stem cells

Abstract: Background Human dental pulp stem cells (DPSCs) have potential applications in tissue regeneration because of their convenient cell harvesting procedures and multipotent capacity. However, the tissue regenerative potential of DPSCs is known to be negatively regulated by aging in long-term culture and under oxidative stress. With an aim of reducing cellular senescence and oxidative stress in DPSCs, an intracellular delivery system for superoxide dismutase 1 (SOD1) was developed. We conjugated SOD1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Smietana et al have reported that loss of SOD1 resulted in weaker bone and lower bone mineral density in mice [64]. SOD1 has been reported to restore osteoblast differentiation by attenuating oxidative stress in human dental pulp cells [65], which is in agreement with our result that treatment with antioxidant agent NAC was able to rescue doxorubicin-mediated decrease in osteoblast differentiation. An inverse relationship was noted between TGFβ1 and SOD1 activity in radiation-mediated fibrosis models [66], [67].…”
Section: Discussionsupporting
confidence: 92%
“…Smietana et al have reported that loss of SOD1 resulted in weaker bone and lower bone mineral density in mice [64]. SOD1 has been reported to restore osteoblast differentiation by attenuating oxidative stress in human dental pulp cells [65], which is in agreement with our result that treatment with antioxidant agent NAC was able to rescue doxorubicin-mediated decrease in osteoblast differentiation. An inverse relationship was noted between TGFβ1 and SOD1 activity in radiation-mediated fibrosis models [66], [67].…”
Section: Discussionsupporting
confidence: 92%
“…These data are in accordance with previous findings that p16, p53 and p21 are highly expressed in senescent dental pulp cells (Mas-Bargues et al, 2017;Muthna et al, 2010). Conversely, downregulation of p53-p21 decreased senescence of dental pulp stem cells (Choi et al, 2012). Meanwhile, p16 knockdown significantly reduced senescence-related dysfunction of dental pulp mesenchymal stem cells (Feng et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…However, SOD-1, Cat-1, and NOS3 were considered in our study, due to their close correlation with angiogenesis and osteogenesis (Choi et al, 2012;Fernández et al, 2009;Gabryel et al, 2016;Ilyas et al, 2016). Moreover, the SOD-1 demonstrated a protective effect in HUVECs under oxidative stress and oxygen deprivation, reducing apoptosis of endothelial cells (Gabryel et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…We also investigated the effect of ionic silicon on gene expression of antioxidant, superoxide dismutase-1 (SOD-1), catalase-1 (Cat-1), and nitric oxide synthase-3 (NOS3) produced by endothelial cells. These oxidative stress markers play a relevant role in the reduction of deleterious oxidative stress and facilitation of angiogenesis and osteogenesis during the tissue-healing process (Choi, Lee, Chung, & Park, 2012;Diwan, Wang, Jang, Zhu, & Murrell, 2000;Fernández, San Miguel, & Fernández-Briera, 2009;Matsunaga et al, 2002;Murohara et al, 1998).…”
mentioning
confidence: 99%